Jam making quality of four varieties of mangoes - Andaya, Cora J.; Guzman, Matilde P. (1964)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Jam; Mango; Mango -- Preservation